2012
DOI: 10.1029/2011jb008940
|View full text |Cite
|
Sign up to set email alerts
|

Isolating along‐strike variations in the depth extent of shallow creep and fault locking on the northern Great Sumatran Fault

Abstract: The Great Sumatran Fault system in Indonesia is a major right‐lateral trench‐parallel system that can be divided into several segments, most of which have ruptured within the last century. This study focuses on the northern portion of the fault system which contains a 200‐km‐long segment that has not experienced a major earthquake in at least 170 years. In 2005, we established the Aceh GPS Network for the Sumatran Fault System (AGNeSS) across this segment. AGNeSS observes large displacements which include sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 34 publications
3
89
0
6
Order By: Relevance
“…The estimated stress drop in the current work was relatively small compared to those found in other studies (e.g., Allmann and Shearer 2009). In this region, Ito et al (2012) observed that the creep region, which is close to the broken segment, may be relatively weaker than other regions. Our estimated low stress drop may thus be consistent with that reported by Ito et al (2012).…”
Section: Static Stress Dropsupporting
confidence: 32%
See 4 more Smart Citations
“…The estimated stress drop in the current work was relatively small compared to those found in other studies (e.g., Allmann and Shearer 2009). In this region, Ito et al (2012) observed that the creep region, which is close to the broken segment, may be relatively weaker than other regions. Our estimated low stress drop may thus be consistent with that reported by Ito et al (2012).…”
Section: Static Stress Dropsupporting
confidence: 32%
“…In this region, Ito et al (2012) observed that the creep region, which is close to the broken segment, may be relatively weaker than other regions. Our estimated low stress drop may thus be consistent with that reported by Ito et al (2012).…”
Section: Static Stress Dropmentioning
confidence: 94%
See 3 more Smart Citations